P98. Measurement of cerebral ventricular sizes and parenchymal abnormalities on bedside by ultrasound sonography in patients with craniectomy: Comparison with CCT. Issue 8 (August 2015) - Bendella, H.; Hartmann, A.E.; Spreer, J.; Rommel, N.; Weber, F.
<x xml:space="preserve">Abstract</x> Introduction In patients with craniectomy ventricular size and parenchymal abnormalities are reliably estimated by CCT or MRI. Both techniques are time consuming; CCT involves frequent radiation exposure. Measurement of ventricular sizes or parenchymal abnormalities by ultrasound sonography is rarely performed. Aim of the study To compare data of measurements of the ventricular size and anatomic structures by ultrasound sonography and CCT in patients (n = 62) with craniectomy following traumatic or vascular accidents. Method Transcranial Duplex sonography (Hitachi-EUB 5000+C; 5-2/Abdominal probe; 1.4 MHz) over the craniectomized hemisphere. Documentation of land marks such as alteration of parenchymal structure, extravascular blood accumulation, hygroma, ventricular diameter, midline shift. Data of ventricular diameter were correlated with measurements obtained by CCT. Results Sonography of the brain's structures and vessels by ultrasound sonography provide sharp outlined pictures which can be compared to CCT imaging with high reliability. Aneurysms larger than 10 mm in diameter were identified in some cases. The correlation of the diameter of the ventricles of the craniectomized and the contralateral side between ultrasound measurement and CCT was high (correlation coeffizient 0.826 for the first and 0.959 for subsequent measurements). In repetitive studies of the ultrasound measurements over a few days (without repetitive CCT), the stability of the diameter was high. Alteration of the horizontal body position between zero and 45 degrees did not affect the diameter of the ventricles. Midline shifts were detected with high reliability. Quantitative measurement of the blood flow velocity in the large intracerebral vessels using the Doppler modus was possible. Summary B-mode ultrasound measurements of the ventricular size, the parenchyma and of the blood flow velocity in patients with craniectomy deliver reliable quantitative results for clinical neurosurgical and neurological decisions and may economize indication for frequent CCT.